An evaluation of 3D modelling in patients with locally advanced pelvic malignancy undergoing surgical resection - Clifford, Rachael Elizabeth; Fretwell, Victoria; Gul, Sadia; Coop, Amanda; Borg, Phillip; Clouston, Hamish; Sutton, Paul A. (Frontiers in Oncology, 2026)
BackgroundSurgery for locally advanced pelvic malignancy is complex, requiring careful operative planning and effective patient consent. Traditional two-dimensional (2D) imaging can limit understanding of tumour-organ relationships for both clinicians and patients. Three-dimensional (3D) reconstructed imaging may have a role in enhancing surgical planning, patient understanding and trainee education.MethodsAdult patients with locally advanced rectal or anal cancer undergoing planned resection at a UK tertiary cancer centre were prospectively identified. CT scans were reconstructed into interactive 3D models using the Visible Patient™ platform. Models were reviewed by surgeons and trainees prior to outpatient consultations and then demonstrated to patients during the consent process. Surgeons, trainees, and patients completed structured questionnaires incorporating Likert-scale responses and free-text feedback. Qualitative data were analysed thematically.ResultsFifteen patient-specific pelvic models were created, with feedback obtained from all surgeons and trainees and from 13 patients. Patient responses were overwhelmingly positive, with median scores of 9–10/10 for realism, understanding of disease and surgery, and perceived benefit during consultation. Thematic analysis highlighted improved understanding, empowerment, and engagement in decision making. Surgeons rated the models moderately for operative planning but highly for trainee education and patient communication. No operative plans were altered following model review. Trainees reported strong educational value, while radiologists noted limitations in segmentation accuracy for intraluminal disease.ConclusionCT-based 3D reconstructed pelvic models provide substantial benefit in patient education and shared decision making for complex pelvic cancer surgery, with additional value as a training tool. Further studies are warranted to define their role in operative planning and cost-effective implementation.